Effect of Amyloid Protein Fibrils on the Quality of Frozen Minced Meat - WU Xiao, LIU Zhanghanyu, LIU Shuo, WANG Mengting, SUN Xiaoshuai, LI Teng (Shipin Kexue)
In this study, amyloid protein fibrils (APFs) were prepared from whey protein isolate (WPI). The microstructure of APFs was characterized by transmission electron microscopy (TEM), which confirmed the formation of non-branching nanofibers. The differences in secondary structures between WPI and APFs were investigated by circular dichroism (CD) and Fourier transform infrared spectroscopy (FTIR). Compared with WPI, APFs had less α-helices and more β-sheets. The free radical scavenging activity of APFs was higher than that of WPI. The ice recrystallization inhibition (IRI) activity of APFs, as evaluated by the splat assay, was significantly stronger than that of WPI, and the higher the incubation temperature, the greater the difference in IRI activity. The color, water-holding capacity (WHC), disulfide bond content, thermal gelation characteristics, and water distribution of minced pork added with APFs at 0%, 1.0%, 3.0%, or 5.0% were measured after freeze-thaw treatment. The results showed that APFs could significantly increase the WHC, improve the thermal gelation characteristics, and reduce protein oxidation without significantly changing the color of frozen minced meat. Therefore, APFs are a potential excellent cryoprotectant for minced meat.